2011
DOI: 10.1021/ja202154j
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Gate: Framework Flexibility in ZIF-8 Explored by Experiments and Simulations

Abstract: ZIF-8 is a zeolitic imidazole-based metal-organic framework with large cavities interconnected by narrow windows. Because the small size of the windows, it allows in principle for molecular sieving of gases such as H(2) and CH(4). However, the unexpected adsorption of large molecules on ZIF-8 suggests the existence of structural flexibility. ZIF-8 flexibility is explored in this work combining different experimental techniques with molecular simulation. We show that the ZIF-8 structure is modified by gas adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

73
887
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,009 publications
(966 citation statements)
references
References 16 publications
73
887
3
3
Order By: Relevance
“…In contrast to many MOFs, which are water soluble or thermal unstable, ZIFs (e.g. ZIF-8) owe a high chemical stability, high specific surface area and excellent porosity [8,9]. ZIF-8 particles, consisting of zinc and 2-methylimidazole (2-Hmim), is a prototypical subclass of ZIFs with a sodalite (SOD) topology similar to some aluminosilicate zeolites, where T-O-T bridges (T = Si, Al, P) are replaced by Zn-Im-Zn [10].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to many MOFs, which are water soluble or thermal unstable, ZIFs (e.g. ZIF-8) owe a high chemical stability, high specific surface area and excellent porosity [8,9]. ZIF-8 particles, consisting of zinc and 2-methylimidazole (2-Hmim), is a prototypical subclass of ZIFs with a sodalite (SOD) topology similar to some aluminosilicate zeolites, where T-O-T bridges (T = Si, Al, P) are replaced by Zn-Im-Zn [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several reported MOFs possess dynamic constituents, e.g., bridging ligands that can rotate, while maintaining an approximately rigid unit cell (18,(24)(25)(26)(27)(28)(28)(29)(30)(31)(32)(33)(34). Nuclear magnetic resonance (NMR) spectroscopy revealed that aromatic rings in the ligands of MOF-5 (26), IRMOF-3 (27), and MIL-47(V) (35) rotate, resembling an ordered assembly of molecular rotors (36).…”
mentioning
confidence: 99%
“…Owing to the framework flexibility of ZIF-8 phase, molecules with a kinetic diameter larger than the pore size of ZIF-8 such as CH 4 (0.38 nm) could also pass through the membrane. 26 In summary, the LDH layer had a positive influence on the gas separation performance of the prepared ZIF-8 membrane, deserving further exploration. For comparison, a pure asymmetric ZIF-8 membrane was also synthesized on a bare a-Al 2 O 3 substrate without LDH network by secondary growth under identical conditions (details are shown in ESI-6 †).…”
mentioning
confidence: 94%